2017
DOI: 10.13181/mji.v25i4.1385
|View full text |Cite
|
Sign up to set email alerts
|

Management of overactive bladder review: the role of percutaneous tibial nerve stimulation

Abstract: ABSTRAK ABSTRACTOveractive bladder (OAB) is a common condition that is experienced by around 455 million people (11% of the world population) and associated with significant impact in patients' quality of life. The first line treatments of OAB are conservative treatment and anti-muscarinic medication. For the refractory OAB patients, the treatment options available are surgical therapy, electrical stimulation, and botulinum toxin injection. Among them, percutaneous tibial nerve stimulation (PTNS) is a minimall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 41 publications
0
9
1
1
Order By: Relevance
“…The causes of high heterogeneity are also related to the patients' sex, age, and medical history; the severity, duration and previous treatment of OAB symptoms; urodynamic factors, such as detrusor overactivity, bladder capacity, compliance and pressure; and the patients' mental state. Studies have found that the ENS has a better effect on nonneurogenic OAB than on neurogenic OAB [20,30]. However, our results show that the evidence of successful treatment with ENS is the same for neurogenic, nonneurogenic and refractory OAB.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…The causes of high heterogeneity are also related to the patients' sex, age, and medical history; the severity, duration and previous treatment of OAB symptoms; urodynamic factors, such as detrusor overactivity, bladder capacity, compliance and pressure; and the patients' mental state. Studies have found that the ENS has a better effect on nonneurogenic OAB than on neurogenic OAB [20,30]. However, our results show that the evidence of successful treatment with ENS is the same for neurogenic, nonneurogenic and refractory OAB.…”
Section: Discussioncontrasting
confidence: 57%
“…On the other hand, it is also to bear the brunt that standards and units of OAB evaluation items vary [20]. Although the evaluation results are objective for urodynamic evaluation, to a certain extent, the long time and high cost affect the evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Percutaneous tibial nerve stimulation is an office procedure in which electrical stimulation via an acupuncture needle is delivered in twelve 30-minute weekly sessions, followed by monthly maintenance therapy. Industry-supported studies of percutaneous tibial nerve stimulation have reported subjective improvement of 60% (95% CI, 49%-75%), with low rates of transient local adverse events (8.5%) and efficacy similar to that of anticholinergic medications …”
Section: Methodsmentioning
confidence: 99%